Kerjasama Antar Aktor dalam Program Lampung Mengajar - Riki Ependi; Eko Budi Sulistio; Vina Karmilasari (Jurnal Administrativa, 2023)
The education process does not run optimally in remote areas or places that are difficult to access. Various problems that occur in the education sector, one of which is the lack of teaching staff to educate in schools. Lampung Province is one area that is still facing these problems. For this reason, the Dinas Pendidikan dan Kebudayaan Provinsi Lampung issued a breakthrough by launching a program called the Program Lampung Mengajar. In carrying out the Program Lampung Mengajar, because of the incompetence and public perception Dinas Pendidikan dan Kebudayaan Provinsi Lampung. The department cooperates with UPT Pengembangan Karir dan Kewirausahaan Universitas Lampung, and Lembaga Penjamin Mutu Pendidikan Provinsi Lampung. This study aims to analyze the cooperation between actors in the Program Lampung Mengajar, as well as the supporting and inhibiting factors for the sustainability of the collaboration. The research method used is a descriptive research type with a qualitative approach. Data was collected through observation, interviews and documentation. Based on the results of the research that has been done, it can be concluded that the cooperation between actors in the Program Lampung Mengajar has been going quite well according to the predetermined plan, but there are still some principles of cooperation that have not been implemented optimally. Factors that support cooperation between actors in the Program Lampung Mengajar are communication, trust, and commitment. Meanwhile, the factor that hinders cooperation is that the authority is not fully owned.